Analisis Penyebab Terjadinya Cacat Produk Dalam Proses Injection Molding Pada Produksi Fan Blade Radiator di PT XYZ - Ramadhan, Andra Caesar; Rahmadewi, Reni (Peneliti.net, 2024)
Analyzing production data to determine the defect rate of products and the types of defects that commonly occur, and identifying the factors influencing defects in the injection molding process. This study begins with data collection in the Production Department to identify the number of defective products and classify them based on the type of defect. The overall research process can be seen in Figure 1. Data and necessary information are obtained from employees responsible for the injection molding process at PT XYZ. Data collection to identify the causes of product defects is conducted during working hours. Information regarding mold repair processes is collected in the Maintenance Department. Short shots occur when the mold is not completely filled with plastic material during the injection molding process. As a result, the produced product will have incomplete or empty sections. Short shots typically happen due to insufficient plastic material injection, overly fast injection time, or inadequate injection pressure. The common defect type in the injection molding production of fan radiators at PT Denso Indonesia is ‘unbalance,’ often caused by incorrect pin placement in the center of the product.